Transcriptome profiling of gene expression in fall dormant and nondormant alfalfa - Zhang, Senhao (Genom Data, 2014)
Fall dormancy (FD) is an adaptive trait in alfalfa (Medicago sativa L.). It appeared in the regrowth process in late summer or early autumn after alfalfa was harvested. FD affects the biomass accumulation and winter survival in high latitude area. However, the molecular mechanism under FD is still not clear at present. Performing RNA-seq of fall dormant and nondormant alfalfa varieties at different time points, we obtained differentially expressed genes between different FD types or time points. These differentially expressed genes may relate to FD in alfalfa. Here, we provide detailed experimental methods and analysis pipeline in our study (Zhang S et al., De novo Characterization of Fall Dormant and Nondormant Alfalfa (Medicago sativa L.) Transcriptome and Identification of Candidate Genes Relate to Fall Dormancy, submitted for publication) for reproducible research. Data generated in our work provide a resource to help decipher the molecular mechanism of FD in alfalfa.